Digital skills and the development of the research project in postgraduate students - Lucio Ponce, Pilar Amparo (2022)
The accelerated advance of technology requires that for better management, digital skills must be mastered, which allow better access to information found in networks or online. It was formulated as a study objective to determine the relationship between digital skills and the development of the research project in postgraduate students. The methodology was a quantitative approach with a correlational design, which was applied to a sample of 100 postgraduate students from the Universidad Nacional Mayor de San Marcos, to whom a questionnaire and rubric were applied to measure their levels of achievement. The results allowed us to find a correlation of 0.591 between the variables. It was concluded that there is a relationship between digital skills and the development of the research project in postgraduate students.